THE CONTRIBUTIONS OF LISTENING AND READING VOCABULARIES TO LISTENING COMPREHENSION OF CHINESE EFL STUDENTS. Issue 2 (4th May 2021) - Bian, Xu; Cai, Xiaojun; Cai, Dianmei
Abstract : The study investigated the relationship between listening and reading vocabularies and their contributions to English listening comprehension of advanced Chinese EFL learners from two universities in China. Measures of reading and listening vocabularies consisted of 5, 000 and academic vocabularies. Two tasks involved in the listening comprehension test were gap-filling and multiple-choice. Results showed the moderate correlation between listening and reading vocabularies; Chinese EFL learners' reading vocabulary knowledge outperformed the listening counterpart. Listening academic vocabulary made a unique contribution to the performance on both the gap-filling task and the entire listening section above and beyond other subcategories of vocabulary. Reading vocabulary was not a predictor of the multiple-choice task. However, the significant effect of reading vocabulary on the gap-filling task suggested that the task might not be an appropriate instrument to assess learners' listening skill.